Optimization of limonene biotransformation for the production of bulk amounts of α-terpineol. (December 2019) - Molina, Gustavo; Pessôa, Marina G.; Bicas, Juliano L.; Fontanille, Pierre; Larroche, Christian; Pastore, Gláucia M.
Graphical abstract: Highlights: Bioprocess for α-terpineol production, a commercially important monoterpene alcohol. Effect of medium composition and cultivation conditions in α-terpineol production. Optimization process for the bioproduction of α-terpineol from limonene. Advances in the bioprocess using biphasic system for limonene bioconversion. One of the highest production of the bioaroma α-terpineol already reported. Abstract: The biotransformation of R -(+)-limonene into high concentrations of R -(+)-α-terpineol by Sphingobium sp. was investigated in order to optimize the main process variables (pH, biocatalyst concentration, substrate concentration, temperature and agitation). This strategy comprised the screening of variables by a Plackett-Burman design followed by a Central Composite Design. The statistical analysis showed that the optimal α-terpineol production were at 28 °C and pH 7.0, with a limonene concentration of 350 g/L of organic phase agitation of 200 rpm and a biocatalyst concentration of 2.8 g/L of aqueous phase (OD600 = 8). Further trials showed that the R -(+)-α-terpineol concentration was higher (240 g/L after 96 h) when using a ratio of 1:3 (v.v −1 ) of organic:aqueous phases. However, the total production and yield (in terms of biomass) of α-terpineol would be maximized for an aqueous:organic ratio of 1:1. The experimental design optimization adopted herein was an effective tool for this type of study.